2020
DOI: 10.1371/journal.pone.0231169
|View full text |Cite
|
Sign up to set email alerts
|

Quantile graphs for EEG-based diagnosis of Alzheimer’s disease

Abstract: Known as a degenerative and progressive dementia, Alzheimer's disease (AD) affects about 25 million elderly people around the world. This illness results in a decrease in the productivity of people and places limits on their daily lives. Electroencephalography (EEG), in which the electrical brain activity is recorded in the form of time series and analyzed using signal processing techniques, is a well-known neurophysiological AD biomarker. EEG is noninvasive, low-cost, has a high temporal resolution, and provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 53 publications
2
33
0
3
Order By: Relevance
“…They also verified that as the time series changes from periodic to chaotic, the corresponding networks, initially regular, become more and more random with larger values of the average path length 10 and clustering coefficient. The work developed by Campanharo, Doescher, and Ramos (2018) and Pineda, Ramos, Betting, and Campanharo (2020) takes advantage of the QGs to classify EEG data.…”
Section: Mapping Univariate Time Series Into Complex Networkmentioning
confidence: 99%
“…They also verified that as the time series changes from periodic to chaotic, the corresponding networks, initially regular, become more and more random with larger values of the average path length 10 and clustering coefficient. The work developed by Campanharo, Doescher, and Ramos (2018) and Pineda, Ramos, Betting, and Campanharo (2020) takes advantage of the QGs to classify EEG data.…”
Section: Mapping Univariate Time Series Into Complex Networkmentioning
confidence: 99%
“…Nonetheless, visual analysis of EEG data is time-consuming, requires specialized training, and is error-prone [16][17][18]. However, we can consider automatic evaluation of EEG time series using modern classification algorithms, which can help to improve the efficiency and accuracy of AD and SZ diagnosis, as verified in previous works [19][20][21][22].…”
Section: Introductionmentioning
confidence: 87%
“…Kim et al [ 45 ] demonstrated that selected set of features from EDA signal can be used as a good biomarker for automatic detection of major depressive disorder using a decision tree classifier. Pineda et al [ 46 ] presented a machine learning model for diagnosis of Alzheimer’s disease using EEG signal. They extracted five typological network features from quantile graphs of EEG signal and presented them to SVM classifier to detect the disease using data collected from 24 healthy and 24 patient subjects.…”
Section: Related Workmentioning
confidence: 99%